'A Brave New World for Chinese Joint Operations'. Issue 1 (2nd January 2017) - Wuthnow, Joel
ABSTRACT: A key organizational challenge for all modern militaries is instituting an effective command-and-control (C2) structure for joint operations. China has been a relative latecomer to joint operations, with a persistent weakness in joint C2. Reforms launched in early 2016 sought to overcome this challenge by establishing a permanent two-level joint C2 structure. Although not a 'tipping point' that will lead ineluctably to stronger operational effectiveness, this reform is nonetheless an important milestone in an evolutionary process towards better PLA joint operations. The result could be added operational challenges for several of China's neighbors and the United States.